HUBUNGAN ANTARA MINAT BELAJAR DENGAN HASIL BELAJAR PADA MATA PELAJARAN IPA SISWA SDS AMKUR BENGKAYANG - Koleta Trivanila Bella (CV. ADIBA AISHA AMIRA, 2024)
This research aims to determine the relationship between interest in learning and learning outcomes in science subjects for class V students at SDS Amkur Bengkayang. This research uses quantitative methods with a correlational design. The subjects of this research were 85 class V students at SDS Amkur Bengkayang. Data collection was carried out using questionnaires to measure interest in learning and tests to measure student learning outcomes. The results of data analysis show that there is a significant relationship between interest in learning and learning outcomes in science subjects for SDS Amkur Bengkayang students. Based on the results of the Pearson product moment correlation test, a correlation coefficient value of 0.65 was obtained, which means there is a moderate positive relationship between interest in learning and learning outcomes. This shows that the higher the student's interest in learning, the higher the learning outcomes obtained by students in science subjects. Thus, interest in learning is an important factor that influences student learning outcomes. Therefore, teachers and schools need to pay special attention to increasing students' interest in learning through various learning strategies that are interesting and relevant to students' daily lives.